PENERAPAN EMPOWERING LEADERSHIP TERHADAP TURNOVER INTENTION PADA GENERASI Z - Putri, Agnesia Retno Yulianing; Fajri, Musholin Dzul Jalali; Dasmadi, Dasmadi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research aims to analyze the impact of empowering leadership application on turnover intention among Generation Z. This generation comprises young employees today and exhibits high propensities to leave, thereby negatively affecting company stability and performance. The study examines how various leadership styles can influence Generation Z's inclination to depart from their organizations. This study utilizes relevant data analysis from previous research. The results demonstrate that empowering leadership plays a crucial role in reducing turnover intention among Generation Z. Empowering leadership has been shown to promote positive perceptions of superiors, enhance self-confidence, and foster attachment to the company among employees. This research aims to provide insight and assist future researchers in understanding the relationship between empowering leadership and turnover intention within the Generation Z era.